Surface enlargement of a new arterialised venous flap by the surgical delay method - Lalković, Mikica; Kozarski, Jefta; Panajotović, Ljubomir; Višnjić, Milan; Djurdjević, Dragan; Djordjević, Boban; Šijan, Goran; Gačević, Milomir; Milićević, Saša; Stojiljković, Vladimir; Maljković, Igor (Vojnosanitetski pregled, 2017)
Background/Aim. The delay method is a surgical, pharmacological and combined method that includes two or more time separated phases, which gives bigger flap surface. In our research we explored the possibility of flap surface enlargement in a new arterialised venous flap (AVF) on an experimental rabbit ear model by the delay surgical method. The aim of this research was to establish vitality surface of our AVF and to maintain the difference in flap vital surface between AVF flaps, with or without performing the delay surgery method. Methods. We used both ears of “Big Chinchilla” rabbits in 10 experimental male animals, divided into two groups, average weight 3–3.5 kg, and average age 8–10 months. In the first (experimental) group, a venous flap was arterialised by our method. In the second (control) group, the venous flap was arterialised 14 days after the delay surgical method. AVF surface was measured on the 1 and 14 days by the method of trapezoid rule. Results. Vital surface on our AVF experimental model was bigger than 87% of elevated flap surface after the delay surgical method. Vital surface on AVF without delay on our experimental model was bigger than 30% of elevated flap surface (p < 0.001). Conclusion. Analysis of previous experimental models on the rabbit ear, non-delayed and delayed (to enlarge flap surface) led us to conclusion that previously created experimental models of non-delayed AVF are hemodynamically negative. Our experimental non-delay AVF model is hemodynamically more positive than previously created models of non-delay AVF and provides better conditions for AVF survival and enlargement of vital flap surface of elevated flap. On the other hand, surgical delay method significantly enlarges vital surface of AFF.